STUDI KUALITAS MINYAK GORENG DENGAN MENGGUNAKAN SPEKTROFOTOMETER - -, Rahmaniah (Fakultas Sains dan Teknologi UIN ALauddin, 2011)
The aim of this research to investigate the quality of coconut oil and palm oil through its measurement of the wavelength spectrum. Spektrofotomer is used to measure the wavelength spectrum, before and after used.The samples are fresh oil, and expired oil. Analysis of the quality of coconut and Â palm oil based on wavelength spectrum show that caconut oil oil is better than palm oil. Analysis of the quality of coconut oil and palm oil show thatÂ palm oil to sample use of coconut oil not containing compounds melanoidin while palm oil for one used melanoidin containing compounds have been found in wavelength of 540 nm which is a green area.Keywords: quality,oil, spectrophotometer.